The Impact of Strategic Planning on Firm Performance: An Empirical Analysis - Vanarse, Renuka Amit; Thakre, Shital Vishnupant; Thorat, Neelesh Balasaheb; Deshpande, Pooja Vaibhav (Journal of Neonatal Surgery, 2025)
Strategic planning has been largely regarded as a significant management process that is able to assist organizations in stating the long term objectives, allocation and imposing changes that take place in business environments. The paper is a qualitative research, as discussed due to the influence of strategic planning on the performance of the firms; it is grounded on financial, operational, and competition performance. This paper justifies the use of the statistical approach, such as correlation and regression analysis, due to the fact that the second data in the study will be gathered through structured questionnaires of selected companies, which will be used to analyze the association between practices of strategic planning and the indicators of organizational performance. The findings indicate that formal strategic planning is strongly, positively connected to the performance of the firm and this substantiates the argument that the company with clear vision, mission, environmental scanning, and the mechanisms of implementation clearly are doing well in comparison with the firms with bad or weak planning processes. The study also adds that strategic planning enhances the quality of the decision making process, efficiency of the operations and sustainability. The results may benefit the current literature by providing empirical evidence of the efficiency of strategic planning as a performance-boosting tool and translate to some practical value to the managers, who are willing to enhance the organizational outcomes through the use of systematic planning techniques